ANALISIS BRAND ASSOCIATION BUS RAPID TRANSIT (BRT) DI KOTA BANDAR LAMPUNG - Yunada Arpan (GEMA : Jurnal Gentiaras Manajemen dan Akuntansi, 2014)
To cope with traffic jam in Bandar Lampung, the government try to develop its transportationsector by building and operating mass transportations such as Bus Rapid Transit (BRT) or was alsoknown as Trans Bandar Lampung.However, after two years of operation Trans Bandar Lampung has not been able to providemaximum services yet. The bad aspect of services is closely related to weak planning. Headwayproblem, travel time, the getting on and off of the passengers, and access to / from the bus stopdoes not even support the existence of a BRT system that has not been strictly controlled yet.Based on examination of 10 BRT Bandar Lampung associations, there are 3 associationsthat make up a very strong brand image, namely Vehicle Quality, Timeliness and Services